1997
DOI: 10.1016/s0741-5214(97)70305-7
|View full text |Cite
|
Sign up to set email alerts
|

Early rupture and degeneration of cryopreserved arterial allografts

Abstract: Arterial allografts are used in vascular surgery to solve a major problem: vascular reconstruction in the infected area. To palliate the unavailability and to reduce the risk of viral disease transmission, vascular allografts are currently cryopreserved and stored in tissue banks. In our recent clinical experience, we observed several cases of rupture and degeneration of cryopreserved arterial allografts. All indications are that current cryopreservation protocols are probably the cause for these degenerations. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 3 publications
0
30
0
1
Order By: Relevance
“…However, some clinical observations reported cases of mechanical modifications of allografts (i.e. fissuring, rupture, aneurysm) (Lehalle et al 1997). Whether the cryopreserved procedures modify viscoelastic and inertial wall properties and geometrical arterial properties remains controversial (Blondel et al 2000;Buja´n et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, some clinical observations reported cases of mechanical modifications of allografts (i.e. fissuring, rupture, aneurysm) (Lehalle et al 1997). Whether the cryopreserved procedures modify viscoelastic and inertial wall properties and geometrical arterial properties remains controversial (Blondel et al 2000;Buja´n et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation indications in these patients comprised infectious aneurysms of the native aorta (3) or prosthetic graft (7), congenital heart disease (4) or other (3). Since Lehalle et al reported early dilation and rupture of arterial cryopreserved homografts in three patients [18], accurate patient-follow up by means of computed tomography or magnetic resonance angiography to determine the individual fate of aortic homografts may be recommended.…”
Section: Resultsmentioning
confidence: 99%
“…The Italian Collaborative Homograft Group reported in 1998, that fresh and cryopreserved grafts behaved similarly with regard to complications (Chiesa et al 1998), contradicting the view of Lehalle et al who felt that it was cryopreservation which led to degeneration and early rupture (Lehalle et al 1997).…”
Section: Recent Allograft Experiencementioning
confidence: 97%